The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s12887-020-02357-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcobalamin deficiency with two novel mutations in the TCN2 gene in a Chinese girl with abnormal immunity: a case report

Abstract: Background Transcobalamin (TC) transports vitamin B12 from blood into cells. TC II deficiency is a rare autosomal recessive disorder. It is characterized by failure to thrive, diarrhoea, pallor, anaemia, pancytopenia or agammaglobulinemia. It is usually confirmed by molecular analysis of the TCN2 gene. We report a 2-month-old girl with two novel mutations, which were first reported in humans. Case presentation We present a 2-month-old Chinese girl with pancytopenia, severe combined immunodeficiency disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Intriguingly, mutation (loss of function) of this gene result in transcobalamin deficiency that leads to an abnormal immunity in the individuals. 39 Our result showed that down regulation of TCN2 is associated with worse survival outcome (Figure 3(h)).…”
Section: Discussionmentioning
confidence: 55%
“…Intriguingly, mutation (loss of function) of this gene result in transcobalamin deficiency that leads to an abnormal immunity in the individuals. 39 Our result showed that down regulation of TCN2 is associated with worse survival outcome (Figure 3(h)).…”
Section: Discussionmentioning
confidence: 55%
“…Later, when transcobalamin defect and its associated increased homocysteine level was suspected, plasma homocysteine level was measured using a separate specific test. Less than 60 patients and 50 TCN2 variants have been reported worldwide in which many cases were reported from regions with a high rate of consanguinity, including Turkey [1,2,[11][12][13][14]. To our knowledge, the present patient is the first case report from a Southeast Asian country with a novel TCN2 variant, c.428-2A > G. The variant was subsequently submitted to ClinVar database and now is accessible using a number SCV001981507 (https:// www.…”
Section: Discussionmentioning
confidence: 99%
“…Nongmaithem SS et al observed that variants in the B12-binding protein gene TCN-2 have also been linked to circulating B12 levels [ 38 ], and that vitamin B12 bioavailability is controlled by the TCN-2 gene [ 39 ]. Alteration in TCN-2 is a mechanism that contributes to the pathogenesis of transcolabamin deficiency, and currently, many cases of transcolabamin deficiency have been reported worldwide [ 40 ], with only one case from China [ 41 ]. According to existing research, the existence of a TCN-2 (CG + GG) variation has been linked to an increased chance of developing Crohn’s disease [ 42 ].…”
Section: Discussionmentioning
confidence: 99%